Mutation Identification in A 5-Generation Pedigree with Autosomal Dominant Retinitis Pigmentosa - 滕云 田虹 王慧 胡晓峰 王嵬 陈燕 杨真荣 (Current medical science, 2003)
An extended 5-generation family has been investigated in which 32 of the 111 family members were diagnosed as having retinitis pigmentosa (RP). The proband was a 58-year old male in whom night-blindness was first observed in early childhood, with almost loss of vision by 52 years of age. The symptoms observed in other family members included night-bllndness, impaired vision and visual field loss. Dementia, digital abnormalities, deaf-mutism and mental retardation were variously diagnosed in a number of individuals with RP. The affected and unaffected family members were tested for mutations in a range of candidate genes. The 8 exons of three candidate genes have been analyzed by polymerase chain reaction-single strand conformation polymorphism(PCR-SSCP) and DNA sequencing techniques. A novel mutation was identified in the rhodopsin gene at codon 52 of exon 1 (TTC-TAC) that resulted in a substitution of Phe to Tyr.